Exotic plants introduction changed soil nutrient cycle and symbiotic relationship with arbuscular mycorrhizal fungi in wetland ecological projects - Jiang, Yuxin; Wang, Mengxuan; Yan, Xue; Liu, Miaodan; Guo, Xiaohong (Frontiers in Plant Science, 2024)
In the process of applying exotic plants to wetland ecological restoration, insufficiently evaluated alien species may exhibit strong competitiveness and fecundity.Once introduced, they can displace native flora, disrupt the original ecological balance, diminish biodiversity, and even induce ecosystem dysfunction. Furthermore, exotic plants have the potential to alter soil microbial community structure, including the composition and activity of beneficial symbiotic microorganisms such as arbuscular mycorrhizal fungi (AMF), thereby impacting soil nutrient cycling and interplant nutrient competition. Here, we conducted three consecutive years of sampling experiments to investigate the succession of AMF communities associated with the invasive plant Spartina alterniflora along an initial introduction chronosequence, and to identify the key environmental factors influencing its response to S. alterniflora invasion. Our findings reveal that early-stage invasion by S. alterniflora alters the composition of soil AMF communities with unclassified_c__Glomeromycetes and Glomus-viscosum-VTX00063 consistently dominating. Additionally, as the duration of introduction increases, the diversity of rhizosphere soil AMF significantly decreases, while its evenness remains relatively stable. It's indicated that soil ω, AN, AK and N/P ratio were the main influencing factors of the integral AMF community. Notably, soil available phosphorus (AP) emerges as a positive influence on the important AMF taxa.The results confirm the mutual feedback effect between the invasion of the perennial herb S. alterniflora and AMF, in which specific AMF assist in nutrient absorption to promote S. alterniflora growth, potentially facilitating its rapid and successful invasion of new habitats. Given the likely differential effects of AMF communities on various plant species, our findings could contribute to anticipating future AMF-mediated effects during the introduction of alien plants.